2016
DOI: 10.1016/j.bbrc.2016.10.127
|View full text |Cite
|
Sign up to set email alerts
|

Potassium depletion stimulates Na-Cl cotransporter via phosphorylation and inactivation of the ubiquitin ligase Kelch-like 3

Abstract: Kelch-like 3 (KLHL3) is a component of an E3 ubiquitin ligase complex that regulates blood pressure by targeting With-No-Lysine (WNK) kinases for degradation. Mutations in KLHL3 cause constitutively increased renal salt reabsorption and impaired K+ secretion, resulting in hypertension and hyperkalemia. Although clinical studies have shown that dietary K+ intake affects blood pressure, the mechanisms have been obscure. In this study, we demonstrate that the KLHL3 ubiquitin ligase complex is involved in the low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 32 publications
3
44
0
Order By: Relevance
“…6, A and B). The latter result is consistent with a previous report (34), and the changes observed are probably due to a decrease in KLHL3-CUL3-RING-mediated WNK4 degradation. However, no changes in the relative abundance…”
Section: Abundance Of Short Wnk4 Variants Is Not Altered By Changes Isupporting
confidence: 93%
“…6, A and B). The latter result is consistent with a previous report (34), and the changes observed are probably due to a decrease in KLHL3-CUL3-RING-mediated WNK4 degradation. However, no changes in the relative abundance…”
Section: Abundance Of Short Wnk4 Variants Is Not Altered By Changes Isupporting
confidence: 93%
“…To evaluate the possible involvement of KLHL3/ CUL3-based ubiquitin ligase in low-K + -mediated NCC induction, we recently analyzed KLHL3 levels in mice on a low-K + diet (Ishizawa et al 2016). Notably, we found that KLHL3 S433-P levels were increased whereas total KLHL3 levels were decreased in the kidney by K + depletion.…”
Section: Mechanisms Regulating Ncc In Dct Cellsmentioning
confidence: 99%
“…Thus, the increase in WNK levels by KLHL3 inactivation and WNK kinase activation induced by the change in intracellular Cl − levels synergistically regulate NCC (Fig. 4) (Terker et al 2015b, Ishizawa et al 2016. A recent study also reported that a Cl − -and SPAK/OSR1-independent pathway activates NCC in hypokalemia (Penton et al 2016).…”
Section: Mechanisms Regulating Ncc In Dct Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…109,110 K þ depletion has also been shown to activate protein kinase C, resulting in increased phosphorylation of KLHL3 at Ser433. 111 The T-shaped, dashed modified arrow structures represent removal of an inhibitory effect. Hypokalemia is associated with an increase in Ang II, which converts WNK4 to an NCC-activating kinase.…”
Section: Effects Of With No Lysine Kinasesmentioning
confidence: 99%